"They Should Be Asking Us": A Qualitative Decisional Needs Assessment for Women Considering Cervical Cancer Screening. (25th June 2018) - Wood, Brianne; Russell, Virginia L.; El-Khatib, Ziad; McFaul, Susan; Taljaard, Monica; Little, Julian; Graham, Ian D.
In this study, we examine from multiple perspectives, women's shared decision-making needs when considering cervical screening options: Pap testing, in-clinic human papillomavirus (HPV) testing, self-collected HPV testing, or no screening. The Ottawa Decision Support Framework guided the development of the interview schedule. We conducted semi-structured interviews with seven screen-eligible women and five health care professionals (three health care providers and two health system managers). Women did not perceive that cervical screening involves a "decision, " which limited their knowledge of options, risks, and benefits. Women and health professionals emphasized how a trusted primary care provider can support women making a choice among cervical screening modalities. Having all cervical screening options recommended and funded was perceived as an important step to facilitate shared decision making. Supporting women in making preference-based decisions in cervical cancer screening may increase screening among those who do not undergo screening regularly and decrease uptake in women who are over-screened.